Measuring the academic digital situation: a knowledge management action - Vega, Omar Antonio (2018)
Information Society and Knowledge, is characterized by the omnipresence of information and communication technologies (ICT) and the intensive use of information and knowledge in the different Sectors. However, the differential way in which communities are incorporated in this globalized and changing environment, with socio-economic inequities and the same digital divide, is indisputable. In such circumstances, the educational institution takes on an unusually important role in producing knowledge and training citizens, which requires it to identify its strengths and weaknesses in its actions consistent with social demands, where its preparation and contribution from the processes of digital inclusion is fundamental point. In view of the above, this document focuses on a contribution to the management of knowledge in the academic field, through two experiences of measuring the digital situation in each population (young middle education students and university professors), with the design and the application of composite indices, which capture generic aspects of the ICT sector and specific to population groups, useful for the design and evaluation of digital inclusion initiatives.